Assessing public opinions of and interest in new vehicle technologies: An Austin perspective - Bansal, Prateek; Kockelman, Kara M.; Singh, Amit (Transportation research. Part C, Emerging technologies, 2016)
•We analyze Austinites’ opinions on connected and autonomous vehicles (CAVs).•We estimate their willingness to pay (WTP) for CAVs and related technologies.•Their average WTP for Level 3 automation is $3300, versus $7253 for Level 4.•Higher-income, tech-savvy males in denser settings are more interested in CAVs.•41% willing to use shared AVs at least once a week at $1/mile, vs. 15% at $2/mile. Technological advances are bringing connected and autonomous vehicles (CAVs) to the ever-evolving transportation system. Anticipating public acceptance and adoption of these technologies is important. A recent internet-based survey polled 347 Austinites to understand their opinions on smart-car technologies and strategies. Results indicate that respondents perceive fewer crashes to be the primary benefit of autonomous vehicles (AVs), with equipment failure being their top concern. Their average willingness to pay (WTP) for adding full (Level 4) automation ($7253) appears to be much higher than that for adding partial (Level 3) automation ($3300) to their current vehicles. Ordered probit and other model specifications estimate the impact of demographics, built-environment variables, and travel characteristics on Austinites’ WTP for adding various automation technologies and connectivity to their current and coming vehicles. It also estimates adoption rates of shared autonomous vehicles (SAVs) under different pricing scenarios ($1, $2, and $3 per mile), choice dependence on friends’ and neighbors’ adoption rates, and home-location decisions after AVs and SAVs become a common mode of transport. Higher-income, technology-savvy males, who live in urban areas, and those who have experienced more crashes have a greater interest in and higher WTP for the new technologies, with less dependence on others’ adoption rates. Such behavioral models are useful to simulate long-term adoption of CAV technologies under different vehicle pricing and demographic scenarios. These results can be used to develop smarter transportation systems for more efficient and sustainable travel.